Frequency control of an isolated micro-grid using double sliding mode controllers and disturbance observer - Wang, Chengshan (2020)
A novel frequency control method based on double sliding mode (SM) controllers is proposed for isolated micro-grids with renewable sources. In the presented technique, the SM pitch angle controller is designed for wind turbine generator (WTG) system to smooth wind power output. The SM load frequency controller (LFC) is constructed for diesel generator system to restore system frequency to normal through the secondary frequency regulation. Then the adaptive SM LFC is redesigned by taking advantage of the disturbance observer and adaptive law to improve dynamic performance of the diesel generator system. The proposed strategy is tested in a typical isolated hybrid micro-grid with both PV and WTG.